2015
DOI: 10.18488/journal.aefr/2015.5.5/102.5.805.815
|View full text |Cite
|
Sign up to set email alerts
|

Causality Analysis of Volatility in Exchange Rate and Stock Market Prices: A Case Study of Pakistan

Abstract: Contribution of the StudyThis study is one of very few studies which have investigated the relationship of the variability of stock prices and exchange rate in Pakistan. In this study, we use conditional standard deviation of each variable as a measure of volatility and then use causality analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 19 publications
3
20
0
5
Order By: Relevance
“…The results of the study showed that there was no long-run relationship between the exchange rate and the stock market prices. A recent study conducted in Pakistan by Khan & Ali (2015) on the relationship between exchange rate and the stock market prices using the Granger causality test showed a bidirectional relationship between exchange rate and stock market prices.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The results of the study showed that there was no long-run relationship between the exchange rate and the stock market prices. A recent study conducted in Pakistan by Khan & Ali (2015) on the relationship between exchange rate and the stock market prices using the Granger causality test showed a bidirectional relationship between exchange rate and stock market prices.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Meanwhile, [21] examines the causality effect between the volatilities of exchange rate and stock market prices in Pakistan by using monthly time series data of Karachi Stock Exchange prices (KSE-100 Index). The results show a bidirectional relationship between the exchange rate volatility and the stock market prices in Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…61.4 (Qayyum & Kamal, 2007;Qayyum & Khan 2014;Din et al, 2010;Ghouse & Khan, 2017;Jebran & Iqbal, 2016;Bhat & Shah 2015;Dar et al, 2013;Aslam, 2104;Ali, 2015). On the other hand, many researchers explored causal linkages between these variables in case of Pakistan see for example (Zubair, 2013;Khan & Ali, 2015;Zia & Rahman, 2011).…”
Section: Introductionmentioning
confidence: 99%